Signaling pathway of targeting the pancreas in the treatment of diabetes under the precision medicine big data evaluation system - Song, Ge; Zhang, Yiqian; Jiang, Yihua; Zhang, Huan; Gu, Wen; Xu, Xiu; Yao, Jing; Chen, Zhengfang (Frontiers in Genetics, 2023)
Diabetes is a chronic non-communicable disease related to lifestyle, environment and other factors. The prediction of diabetes, the improvement of prevention, the reduction of the incidence of diabetes, the formulation of effective prevention and treatment measures, and the reduction of diabetic lesions are important subjects of clinical research on diabetes. The main lesion of diabetes is the pancreas. Inflammation, oxidative stress and other factors can interfere with the conduction of various cell signaling pathways, thereby inducing pancreatic tissue lesions and diabetes. Precision medicine covers epidemiology, preventive medicine, rehabilitation medicine and clinical medicine. In this paper, based on the analysis of big data in precision medicine, the pancreas was used as the target to analyze the signaling pathway for the treatment of diabetes. The analysis was carried out from five aspects: age structure of diabetes mellitus, diabetes blood glucose control standard for type 2 elderly, changes in the number of diabetic patients, the proportion of patients using pancreatic types, and the proportion of patients using pancreatic types. The results of the study showed that targeting the pancreas to treat diabetes reduced the diabetic blood sugar rate by approximately 6.94%